Ethnobotanical Insights into Medicinal Plants usage in Haj Kaddour, Morocco - Benamar, Khadija; Dehbi, Ilham; Azagouagh, Meryem; Lmekkeddem, Younes; Lahlali, Rachid; Ibnsouda Koraichi, Saad; Benamar, Saad; Fikri-Benrahim, Kawtar (Ethnobotany Research and Applications, 2025)
Background: The use of medicinal and aromatic plants (MAPs) in traditional medicine is integral to Moroccan culture. This study examines their use in Haj Kaddour, a rural area in north-central Morocco, and provides detailed ethnobotanical data on the most frequently cited species. Methods: A survey was conducted for the first time in Haj Kaddour, with 94 residents of to assess their use of MAPs. The data was analyzed using plant citation indices, and Multiple Correspondence Analysis (MCA) was applied to explore relationships between plant use and the socio-demographic characteristics of participants. Results: The study found that 68.08% of participants used MAPs. A total of 52 species from 26 families were recorded, with Origanum compactum Benth and Mentha pulegium L. being the most commonly mentioned. Leaves were the most commonly used part, and infusions were the preferred preparation method. Moreover, individuals with low or no MAPs use (<3 species) tended to be male, unmarried, under 20 years old, and highly educated. In contrast, moderate (>4 species) or high (>7 species) users were mainly female, married, over 20, and had lower education levels. A key challenge was the relatively low level of MAPs use among younger, highly educated individuals, which may reflect shifting cultural practices or reduced knowledge transfer across generations. Conclusions: This study highlights the widespread use of MAPs in Haj Kaddour as traditional remedies. The results provide valuable ethnobotanical insights and establish a foundation for further research in pharmacognosy and the development of natural-based therapies. Keywords: Haj Kaddour, ethnobotany, multiple component analysis